Replacement of Professional Photogrammetric Workstations with Low Cost or Free of Charge Photogrammetric Software and Services for Image Triangulation and Image Matching - Kumar, Umesh (Journal on Geoinformatics, Nepal, 2013)
In the modern context of digital technology in the field of surveying and mapping, the technique of digital photogrammetry plays crucial role in all steps of mapping. There are some very expensive as well as low cost and free softwares are available in the market for professional photogrammetric work stations. The image triangulation and image matching is one of the very important steps of photogrammetry for which LPS as a commercial software is available in market. There are some low cost and free software as 123D Catch and Patch Boased Multi View Stereo Softwear (PMVS) also available. So, this paper mainly deals with the accuracy as well as the performance of those software for aerial triangulation and image matching for airborne image data to substitute commercial software for photogrammetric workstations. The accuracy assessment of image orientation, points cloud as well as DSM generated from those points cloud are also performed and compared with all products of LPS as commercial software. Nepalese Journal on Geoinformatics -12, 2070 (2013AD): 42-48